The Far InfraRed Spectroscopic EXplorer (FIRSPEX) - Rigopoulou, D; Tan, B; Yassin, G (Society of Photo-Optical Instrumentation Engineers, 2016)
The Far InfraRed Spectroscopic EXplorer (FIRSPEX) is a novel concept for an astronomy satellite mission that will revolutionise our understanding of the properties of the Interstellar Medium (ISM) and star formation through velocity resolved spectroscopic observations at multi-terahertz frequencies. FIRSPEX comprises a fully cryogenic (~4K) heterodyne payload and a ~1.2 m primary antenna to scan the sky in a number of discreet spectroscopic channels delivering 3- dimensional spectral information. The spectral range selected contains important molecular, atomic and ionic species; the majority of which cannot be observed from the ground. FIRSPEX is UK led with additional contributions from partners throughout Europe. FIRSPEX opens up a relatively unexplored parameter space that will produce an enormously significant scientific legacy by focusing on the properties of the multi-phase ISM, the assembly of molecular clouds in our Galaxy and the onset of star formation topics which are fundamental to our understanding of galaxy evolution.